(untitled) (Biological Sciences - PJSIR, 2009)
A high-performance liquid chromatographic (HPLC) technique with ultraviolet detection incorporating solid phase extraction (SPE) was developed to meet analytical and metrological requirements for routine serum level monitoring of methotrexate (MTX), with several parameters optimised such as temperature, flow rate, composition of the mobile phase and pH of the buffer solution. Two standard curves were constructed to cover the high and low levels of the calibrator range (0.02-600 ?mol/litre). Reproducibility (precision) of the method for intra assay was 2.7; 2.10; 1.38% at the lowest level and 2.11; 3.4; 2.01% at the highest level and for inter assay was 2.8; 2.2; 2.94% at the lowest level and 2.4; 2.74; 2.68% at the highest level; recovery was between 90.47 and 98.53 percent. Response was found linear over the whole range of the calibrator set with a correlation coefficient of 0.999. The limit of quantification and the limit of detection were 0.02?mol/ litre and 0.0063?mol/litre, respectively. The method is suitable for quantification of methotrexate with good accuracy and precision